Modern Organization Theory and Critical Organization Theory - Akdila Bulanov; Afri Wandi Zahri Ramadhan; Nabila Sukma; Putri Varisya (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This article discusses the development of organizational theory, from modern organizational theory to basic organizational theory, and its application. The research background is driven by the evolution of organizations from the post-Industrial Revolution to the digital era, where modernism emphasized efficiency and environmental adaptation, while critical approaches exposed power, capitalist ideology, and worker alienation. The research objective is to analyze the development of organizational theory from the modern to the critical paradigm and its application to contemporary organizational management in Indonesia. The method used is a literature review with a qualitative approach to collect and analyze relevant sources. The research results found that the integration of both theories produces a "critical modernism" framework for sustainable management. Practical implications include recommendations for public and private organizations in balancing productivity with social justice. This research contributes to the development of contextual organizational theory in Indonesia. This theory emphasizes similarity, adaptability, and technological integration, as well as the conceptual emphasis of contingency theory, learning organizations, and transformational leadership. Through this contextual study, it can be concluded that organizational theory has undergone adaptive development in accordance with the surrounding social, economic, and technological dynamics. This article is expected to serve as a reference for academics and practitioners in understanding modern organizational dynamics and critical organizational theory.